2013
DOI: 10.1016/j.bbamcr.2012.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics in heart disease

Abstract: Mitochondrial fission and fusion have been observed, and their importance revealed, in almost every tissue and cell type except adult cardiac myocytes. As each human heart is uniquely dependent upon mitochondria to generate massive amounts of ATP that fuel its approximately 38 million contractions per year, it seems odd that cardiac myocytes are the sole exception to the general rule that mitochondrial dynamism is important to function. Here, I briefly review the mechanisms for mitochondrial fusion and fission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 88 publications
0
90
0
2
Order By: Relevance
“…Why mitochondria undergo fusion and fission is not well understood, but it is hypothesized that fission and fusion allow for complementation of mitochondrial mutations and elimination of dysfunctional mitochondria, thereby preserving functional mitochondrial populations (23). Mitochondrial fission and fusion classically involve the participation of five individual proteins: Drp1, Mfn1, Mfn2, Fis1, and Opa1.…”
Section: Discussionmentioning
confidence: 99%
“…Why mitochondria undergo fusion and fission is not well understood, but it is hypothesized that fission and fusion allow for complementation of mitochondrial mutations and elimination of dysfunctional mitochondria, thereby preserving functional mitochondrial populations (23). Mitochondrial fission and fusion classically involve the participation of five individual proteins: Drp1, Mfn1, Mfn2, Fis1, and Opa1.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dynamics, in particular biogenesis, fusion-fission, and autophagy, play critical roles in cardiac functions (33)(34)(35). Our previous observations of diverse and asynchronous mitochondrial protein turnover in the normal mouse heart led us to conclude that the turnover of individual proteins can influence the homeostasis and dynamics of mitochondria (16,36).…”
Section: Figurementioning
confidence: 92%
“…Since genes that regulate mitochondrial biogenesis and dynamics were altered in KLF4-deficient myocardium ( Figure 1E), we next sought to determine whether KLF4 also regulates mitochondrial biogenesis and dynamics in the heart. It has been reported that these processes are quite rare in the adult myocardium but critical for cardiac adaptation in the postnatal period (5,14,25). Thus, we chose to study perinatal cardiac development, as this period is notable for robust changes in mitochondrial biogenesis and dynamics.…”
Section: Resultsmentioning
confidence: 99%